A method for evaluation of the effects of attachments in aligner-type orthodontic appliance: Three-dimensional finite element analysis. Issue 4 (December 2017) - Goto, Mariko; Yanagisawa, Wakana; Kimura, Hitoshi; Inou, Norio; Maki, Koutaro
Abstract: Purpose: Many patients require esthetic orthodontic treatment. Aligners have recently become widely used in such cases. However, orthodontic treatment occasionally causes unexpected tooth movement called the bowing effect. For example, when premolars are extracted during treatment, molars tend to tip toward the extracted area. Recently, small composite attachments have been recommended with the aim to generate effective orthodontic force to prevent the bowing effect. However, the mechanism of tooth movement with attachments of aligner-type appliances is not yet clear. Materials and methods: In this study, we evaluated the effects of attachments on aligner treatment with finite element analyses. Results: In this study, the computational results with finite element analyses show that the shape and position of attachments have no influence on tensile force and tipping moment. Differences in delicate positioning of attachments changed the analytical results. Conclusions: We suggest that appropriate model setting is important to evaluate the effect of attachment by finite element analyses.